Surfacing development needs of a marginal upland community through participatory tools: The case of village in Samar, Philippines - Cagasan, Editha G.; Gravoso, Rotacio S.; Bales, Milagros C.; Bulayog, Ernesto F.; Ongy, Elvira E.; Alao, Flordelaine T. (Annals of Tropical Research, 2022)
Efforts to alleviate the productivity of marginal uplands necessitate the use of participatory approaches to identify development needs of the community. However, despite the popularity of participatory methods for assessing community resources and needs, the literature lacks information on how it works, especially in the Philippine setting. This study aimed to determine the needs of a marginal upland community and demonstrate the use of the participatory tools. Data were gathered in a marginal upland community in Samar, Philippines whose primary source of livelihood of the residents is farming. Rice is the staple food. The people’s livelihood activities are beset by some threats, including scarcity of water in the area, declining soil fertility of their farms, extreme weather events, and the occurrence of pests and diseases. To augment their livelihood, the people identified livelihood projects, including food processing, vegetable farming, and animal raising. However, results of the resources vulnerability analysis indicate that the assistance needed by the community should go beyond training workshops on crop production, food processing, and animal raising. The assistance should also consider the rehabilitation of the environment, which is now highly degraded. The implementation of a Rainforestation project may be considered to raise food crops and rehabilitate the watershed of the community to address its serious problem of water scarcity. There may also be a need to identify other crops that would survive in the area given its current condition so that the people will have food sources aside from rice. This study has demonstrated that use of participatory tools allows for the collection of in-depth information on community needs and promotes active participation among the participants.